1962
DOI: 10.1021/jf60123a009
|View full text |Cite
|
Sign up to set email alerts
|

Soil Adsorption of Herbicides, The Adsorption of Monuron and Diuron by Hawaiian Sugarcane Soils

Abstract: Administration of Diazinon was discontinued on August 7, 1961. There was no apparent excretion of the insecticide in milk even at the extremely high level of intake. Diazinon is apparently altered in some manner in the digestive system of the dairy cow since the insecticide was recovered from the butterfat separated from milk to which it had been added.A maximum single nontoxic dose of 10 mg. per kg. has been reported by Radeleff (2) for adult cattle. The two cows at the highest level received 8.2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1966
1966
1979
1979

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 3 publications
(4 reference statements)
1
19
0
Order By: Relevance
“…The adsorption of various herbicides by montmorillonite was considerably greater than with illite or kaolinite . Similar observations have been reported by many others (HILL 1956, YUEN andHILTON 1962). Crystalline and amorphous oxides and hydroxides of silica, iron, and aluminum occur in soils as separate phases as well as coatings on surfaces of layer lattice silicates.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…The adsorption of various herbicides by montmorillonite was considerably greater than with illite or kaolinite . Similar observations have been reported by many others (HILL 1956, YUEN andHILTON 1962). Crystalline and amorphous oxides and hydroxides of silica, iron, and aluminum occur in soils as separate phases as well as coatings on surfaces of layer lattice silicates.…”
Section: Introductionsupporting
confidence: 89%
“…These same four substituted ureas were found to have a comparative adsorption ratio inversely related to their solubilities. Studies with Hawaiian sugar cane soils by YUEN and HILTON (1962) and indicated that in all cases there was greater adsorption of diuron than monuron. The solubility of monuron is five times that of diuron.…”
Section: B) Physico-chemical Character Of Adsorbatementioning
confidence: 97%
“…In order to compare adsorption over the full range of concentrations used, both k and 1/n values must be taken into consideration (Yuen and Hilton 1962).…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown for volatile toxi cants like methyl bromide (44), chloropicrin (223), EDB (38, 117, 245), DBCP (116,262), and 1,3-D (136); for semivolatile toxicants like 2-chloro-6-(trichloromethyl)pyridine (72), EPTC (240), and CDEC (67); and for low volatile toxicants such as the chlorinated hydrocarbons (99,142,208) and the urea herbicides (108,263).…”
Section: Goringmentioning
confidence: 97%
“…Usually sorption by clays is readily reversible, whereas sorption by or ganic matter is not (2,87,116,117,168,212,220,245,263). This does not mean that some toxicants cannot eventually be completely desorbed from organic matter.…”
Section: Goringmentioning
confidence: 99%